Strain-engineering Mott-insulating La2CuO4 - O. Ivashko (Nature Portfolio, 2019)
The optimal condition for superconductivity is a long-sought issue but remains challenging. Here, Ivashko et al. demonstrate that the compressive strain to La2CuO4 films enhances the Coulomb and magnetic-exchange interactions relevant for superconductivity, providing a strategy to optimise the parent Mott state for superconductivity.